A Selective Study on Decolorization of Textile Azo Dye using Genetically Modified Brown-Rot Fungi: A Selective Study on Decolorization of Textile Azo Dye using Genetically Modified Brown-Rot Fungi - Sharma, Dr. S. Chacko Vijai (International Journal of Pharmaceutical & Biological Archive, 2019)
Aim: Bioremediation of textile effluents using microorganisms can transfer toxic dyestuffs into non-toxic. Moreover, the discovery of the value of brown-rot fungi in bioremediation has brought a great success in this field. Molecular biology related to brown-rot fungi, especially related to the extraction of genetic material (RNA and DNA), gene cloning, and the construction of genetically engineered microorganisms is especially attractive and thus investigated in recent years. Steam-assisted dry gel conversion of tetraethyl orthosilicate and sodium aluminate to ZSM-5 and ZSM-5 activated carbon composite. Result: The resulting material exhibited hierarchical pore structure with high surface area and porosity as characterized by X-ray diffraction and nitrogen adsorption. The addition of activated carbon enhanced the surface area and adsorption percentage of aqueous lead (Pb2+) and cadmium (Cd2+) from aqueous solution and further from industrial effluents. Conclusion: The co-ordination of the alumina incorporated was analyzed using Al magic-angle spinning nuclear magnetic resonance. ZSM-5/activated carbon composite with high crystallinity was obtained which exhibited high adsorption rates when compared to ZSM-5, activated carbon individually, and their mechanical mixtures.